Stereotype threat affects the learning of sport motor skills - Heidrich, C.; Chiviacowsky, S. (Psychology of Sport and Exercise, 2015)
Studies have shown that stereotypical conditions can affect the performance of academic as well as motor skills (for a review see Chalabaev, Sarrazin, Fontayne, Boiché, & Clément-Guillotin, 2013). The objective of the present study was to investigate the influence of stereotype threat on the learning of a sport skill in women. Participants practiced 15 trials of a soccer dribbling task, and their learning was observed in immediate and delayed retention tests. Before practice, participants were divided into two groups which received instructions introducing the task as either involving athletic speed/power capacities, where women normally perform worse than men (stereotypical condition - ST), or as involving agility/coordination capacities, where women normally can perform similarly than men (nullified-stereotype condition - NST). They also filled out questionnaires measuring self-efficacy. Participants of the ST group showed significant lower motor performance and learning, as well as lower self-efficacy levels, than the NST group. The findings provide evidence that the learning of sport skills can be affected by stereotypical conditions. They add to the growing evidence of the impact of social-cognitive and affective factors on motor skill learning.